Evaluasi Kinerja Dalam Pelayanan Kereta Rel Listrik Eksekutif Jabodetabek - Suliyanti, Rini (Warta Penelitian Perhubungan, 2010)
The Problem that need to be handle at the moment is an unbalance demand for the executive class inrailwm; services accross Jabodetabek during rush hour traffic with the utilities capacity available,which is make low qualihJ factor of service . Conneccted to the problems above, various efforts ha-uebeen made btJ Kereta Api ( Persero), but it was not yet maximum refraction. So this str.A.dy wasconducted to determine the service performance of KRL, Executive Jabodetabek Using Seater Plotanalysis approach, btj set forward the analysis that need attention and imprmiement is the accuracyof trafel time, waiting time, standard rooms and llounge facilities, standards and facilities up dawninformation systems in train, there are variables which are not problematic, but needs tobe preservedis the level of safehJ, standard lighting, and expousure, air circulation, but there are other things thatneed attention is the level of travel speed trains, ticket purchase service information system at thestation, accuraciJ of travel time, waiting time of arrival, facilities for passenger trains up and dawn.Keyword : Level of service, KRL Jabodetabek, Eksekutif Class.